The Influence of School Principals' Leadership on Teacher Job Satisfaction - Nur Purnama Sari; Sagaf S. Pettalaongi; Masmur M (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
This study aims to analyze the influence of principal leadership on teacher job satisfaction at MTs Negeri 3, Donggala. The research employed a quantitative approach with a causal associative design. The population consisted of 27 teachers, all of whom were selected as research participants using a saturated sampling technique. Data were collected through questionnaires, observations, and documentation. Instrument validity and reliability were tested before conducting statistical analysis using SPSS 26. The analysis included descriptive statistics, normality tests, linearity tests, simple linear regression, t-tests, and coefficient of determination tests. The results revealed that principal leadership had a positive and significant effect on teacher job satisfaction, indicated by a significance value of 0.010 (<0.05) and a regression coefficient of 0.605. Furthermore, the coefficient of determination (R²) was 0.239, showing that principal leadership contributed 23.9% to teacher job satisfaction, while the remaining 76.1% was influenced by other factors not examined in this study. These findings indicate that effective leadership practices, including communication, motivation, supervision, and interpersonal support, play an important role in enhancing teachers’ job satisfaction. However, teacher job satisfaction is also affected by broader organizational factors such as work environment, professional development opportunities, welfare, organizational culture, and institutional support. Therefore, improving teacher job satisfaction requires a comprehensive approach that integrates leadership development with organizational improvement strategies within the madrasah context